AB0209 Female Sex Increases The Risk of Forefoot Deformity in Patients with Rheumatoid Arthritis. (15th July 2016) - Inui, K.; Orita, K.; Okano, T.; Mamoto, K.; Sugioka, Y.; Tada, M.; Koike, T.; Nakamura, H.
Abstract : Background: Forefoot involvement in patients with rheumatoid arthritis (RA) is common, and reported to be present in 50–90% of patients without any clear gender predisposition. However, patients with RA that undergo surgical treatment for their forefoot deformities are mostly female, which seems much higher rate than the prevalence of forefoot involvement by arthritis condition. Objectives: In this study we evaluate the factors that contribute to forefoot deformity in RA, and investigate the significance of gender differences in forefoot deformity. Methods: In this cross sectional study, 265 patients (530 feet) with RA (165 females) were enrolled. On AP and lateral standing radiographs of the foot, the angle formed by the first and second (M1/M2) and first and fifth metatarsal bones (M1/M5), the angle formed by the first metatarsal bone and the first proximal phalanx (HV), and the calcaneal pitch angle (CPA) were measured. Patient characteristics and laboratory tests were also analyzed for their potential association with forefoot deformity. As the indications for the surgical treatment of rheumatoid forefoot deformities are strongly influenced by the severity of the hallux valgus deformity, we therefore analyzed patient factors in relation to the measured HV angle. Results: The HV angle was statistically greater in female RA patients than males. Patient age, sex, body mass index, disease duration, Steinbrocker staging, M1/M2 angle, M1/M5 angle, CPA, erythrocyte sedimentation rate, c-reactive protein, matrix metalloproteinase-3, and anti-citrullinated protein antibody measurements were correlated with the HV angle using a single regression analysis. Patient age, BMI, Steinbrocker stage, M1/M2 angle, M1/M5 angle, and the female gender were correlated independently with the HV angle. Conclusions: The hallux valgus deformity observed in patients with RA was more severe in females, which was independent of other patient factors. This finding emphasizes that the female gender is a risk factor for the progression of the rheumatoid forefoot deformity. Disclosure of Interest: None declared